English Private Tutoring in Macao: Perceptions of Senior Secondary Three Students. (March 2019) - Chan, Vivien Nga Man
Purpose: This article examines how individual, school, and social factors shape the perceptions of students in Senior Secondary Three (SS3; in some schools called Form Six [F6]) toward English private tutoring in Macao. Design/Approach/Methods: This is a comparative study of two F6 classes of an English-medium secondary school and four SS3 classes of a Chinese-medium secondary school in Macao, with a total number of 145 students. Mixed-methods approach (questionnaires and interviews) is employed in the study. Findings: The respondents' participation in English tutoring is not very intensive. They prefer to receive government-subsidized after-school tutoring taught by their schoolteachers more than fee-paying English tutoring taught by tutors outside. Low level of social competition and high tertiary enrollment rates contribute to this phenomenon. Students' needs and beliefs in English learning play key roles in determining their receipt of English tutoring. Originality/Value: Teachers may need better understanding of their students' needs so as to design suitable pedagogies. Schools can consider more fully the types of tutoring that they provide for different kinds of pupils. The government-subsidized after-school tutoring could be a plausible way to reduce educational inequality.